Existe correlação entre o ângulo de báscula pélvica, a força e a função dos músculos do assoalho pélvico? - Andrade, Marília Fernandes (2017)
Introduction: Woman during its lifetime undergoes with changes in your body due to external and internal factors that can alter the spine structure, reaching pelvic posture. Objective: to investigate the relationship between pelvic tilt angle, strength and function of pelvic floor muscles in nulliparous women in reproductive phase and primiparous or multiparous women in postmenopausal phase. Methods: Observational and cross-sectional study. Participated in the study 134 women, divided in two groups: 64 postmenopausal women and 70 women in reproductive phase. The pelvic position evaluation was performed by photogrammetry. The participant was positioned at right sagittal plane, in an appropriate place, with predetermined anatomical points marked on the pelvis, the points were: anterior superior iliac spine and posterior inferior iliac spine. The evaluation of Pelvic floor muscles (PFM) was carried out by vaginal digital palpation (Oxford Modified Scale, 0-5 contraction degree) and using a vaginal dynamometer (EMG System Brazil). Urogynecological symptoms (Urinary and sexual) were evaluated through ICIQ Urinary Incontinence - Short Form (ICIQ-UI SF), ICIQ - Overactive Bladder (ICIQ-OAB) and Female Sexual Function Index (FSFI). Results: None of the variables: contraction degree (rs=-0.11, p=0.19), maximum dynamometry (rs=0.01, p=0.92), mean (rs=-0.10, p=0.23) and endurance (rs=-0.01, p=0.86) correlated with pelvic tilt angle. The groups showed different from each other in vaginal digital palpation (p<0,01), on average of dynamometry (p<0,01) and endurance (p<0,01). All three questionnaires (ICIQ-SF, ICIQ-OAB and FSFI) showed a significant difference between groups (p<0.01). Conclusion: The present study results indicate that there is no correlation between pelvic tilt angle, contraction degree and pelvic floor muscles strength in the studied population.